Between-group encounters in Nicobar long-tailed macaque (Macaca fascicularis umbrosus). Issue 6 (2nd November 2018) - Pal, Arijit; Kumara, Honnavalli N.; Mishra, Partha Sarathi; Velankar, Avadhoot D.; Singh, Mewa
Abstract : Group living primates often participate in between-group encounters to defend monopolizable resources. Participation in an encounter is influenced by the density and abundance of resources and the relative fighting ability of groups. We studied between-group encounters in three groups of Nicobar long-tailed macaques ( Macaca fascicularis umbrosus ) in the Great Nicobar Island, with one group, TR, being the focal study group to measure the influence of these factors on between-group encounters. Encounters varied from mutual tolerance to aggressive fights, with females participating less aggressively than males. Sleeping site and vegetation cover were the primary influences on the nature of interaction in the areas where home range overlapped. The initiation and intensity of an encounter were influenced by relative group size. The focal group (TR) was the smallest of the three groups in the area and it actively avoided confrontation with the other two groups (MG and PI), resulting in a lower observed encounter rate than expected. Both the frequency and aggressiveness of encounters was influenced by the number of females cycling and the number of males present in the study group. Inasmuch as encounters were influenced by the number of females and the distribution of food, rather than geography, we conclude that encounters serve to defend food resources and mates rather than that they are examples of territoriality.